Consumer-based optimization and standardization of sweet potato (Ipomoca batatas var. Emitlog) kroepeck - Martinez, Mark Joaquin G.
ABSTRACT The study aimed to develop an acceptable sweet potatoes (Ipomoea batatas var. Emitlog) kroepeck through consumer-based optimization and standardization procedures. The physicochemical properties of an initial kroepeck formulation were determined in the first phase of the study. Response surface methodology (RSM) was used in the optimization of the kroepeck formulation. Mixture constraints of the independent variables used in the study with their corresponding ranges were: 10-80% sweet potato, 20-50% flour, and 20-90% cornstarch. Seven formulations were generated and tested for consumer acceptance and subjected to physicochemical tests. Response models for all the attribute acceptance and moisture content were evaluated to determine the optimum region for the sweet potato kroepeck. Consequently, areas within and outside the optimum area were verified and the optimum formulation was standardized. Results of the RSM showed that the kroepeck mixtures composed of 26.0 - 33.0% sweet potato, 13.0 - 25.3% flour, and 48.0 - 54.0% cornstarch yielded acceptable products. Verification of the prediction models for an acceptable formulation indicated that the models were valid and reproducible with the exception of moisture. However, the moisture content was still retained as studies have cited its significance in the acceptability of extruded snack foods. The model for the kroepeck formulation was able to accurately predict the responses for formulations outside the optimum region but underestimated the values for the optimum product. However, the actual sensory scores for the optimum product show that it was more acceptable than products outside the optimum region and as such indicated that the tested region can still be considered as optimal. The results of the standardization phase of the optimized formulation indicated that it was repeatable. The final product consisted of 33% sweet potato, 52% cornstarch and 15% flour which had a light yellow color with a mean water activity of 0.404 and a final moisture content of 9.61%.